Antibacterial and cytotoxicity activity in macroalgae extracts: perspectives for the use against pathogenic bacteria from shrimp farms (Litopenaeus vannamei) (Acta Scientiarum. Biological Sciences, 2018)
Some infections caused by pathogenic microorganisms might shows high prevalence in farmed shrimp environments, compromising production and causing economic losses. Therefore, the search for compounds with antibiotic activity has become intensive, following the record of new antimicrobial-resistant bacteria. The study of those bioactive compounds in marine macroalgae has produced satisfactory results, such as the discovery of antibacterial activity against multiresistant strains. Accordingly, this study aims to research antibiotic activity in macroalgae extracts of Chlorophyta, Phaeophyta and Rhodophyta found in the coast of Ceará and also to evaluate the cytotoxicity activity against bacterial strains (Vibrio sp.) from shrimp farms (Litopenaeus vannamei). The extracts cytotoxicity was also evaluated. The results prove that there was antibacterial activity in ethanolic, acetonic, hexanic and methanolic extracts against bacterial strains of Vibrio with multiple resistance profile as well as displaying low cytotoxicity.